Pengaruh Konseling Kelompok Teknik WDEP (Wants Direction Evaluation Planning) Terhadap Peningkatan Perilaku Tanggung Jawab dalam Penyelesaian Tahfidz - Khairunnisa, Sabrina; Tawil, Tawil; Nuraini, Paramita (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of group counseling with the WDEP technique on increasing responsible behavior in completing tahfid. The research method is quantitative. The type of this research is experimental research. The design of this research uses Pre-Experimental One Group Pretest Posttest. The subject of this research is class 2E MTs Muhammadiyah 02 Patean Kendal totaling 30 students. Sampling. The data collection method is using a questionnaire. Data analysis is using the Paired Sample T-Test. The conclusion of this study is that group counseling with the WDEP technique has no effect on increasing responsible behavior in the completion of low tahfid. The significance results show 0.37 more than 0.05, so it can be concluded that Ho is accepted, Ha is rejected, meaning that group counseling with the WDEP technique has no effect on increase responsibility in completing tahfid after being given treatment using group counseling services with the WDEP technique. The reasons the results of this study have no effect are as follows; the time used for counseling services at night during the night and virtual breaks and, and also the time limited by the cottage or the place used for research due to the effects of this pandemic.